Parents' Investment in English Language Schooling: A Study at SMP Alam Lubuklinggau - Irfan, Abdullah; Mirizon, Soni; Amrullah, Amrullah (Universitas Hamzanwadi, 2023)
This qualitative study investigates the motivations of parents choosing English language education for their children at SMP Alam Lubuklinggau, a school increasingly integrating English into its curriculum. Focusing on 34 independent parents, who enrolled their children without expecting tangible incentives such as tuition fee reductions or housing provisions, the study explores the rationale behind these educational choices. Data were gathered through a combination of observations and one-to-one semi-standardized interviews, offering in-depth insights into parental perspectives. Thematic analysis was employed to interpret the findings, highlighting the parents’ emphasis on language acquisition, particularly in enhancing their children's English proficiency. The results demonstrate that parents predominantly view the enrollment at SMP Alam Lubuklinggau as an investment in their children's future language skills. This investment decision was found to be significantly influenced by the parents' unique characteristics, social roles, affiliations, and financial standing. The study concludes that the primary driving force behind these educational decisions is the desire to equip children with essential language skills in an increasingly globalized world, rather than short-term benefits or financial incentives